Novel variations in the PLOD1, COL1A1, COL5A2 and COL4A1 genes related to keratoconus - Lin, Qinghong; Wang, Xuejun; Peng, Xiaoliao; Han, Tian; Sun, Ling; Zhang, Xiaoyu; Zhou, Xingtao (Frontiers in Genetics, 2025)
PurposeTo investigate the genetic characteristics of four Chinese families affected by keratoconus (KC).MethodsIn the four families affected by KC, medical records, clinical observations, and blood samples were collected from all individuals. One hundred subjects without KC served as healthy controls. All controls and subjects in the four families underwent whole exome sequencing of their genomic DNA and polymerase chain reaction to confirm the variants. All variants were analyzed using online software; and in silico predictions of three-dimensional protein structures were performed.ResultsThe clinical manifestations in those first-degree family members of the probands were atypical. The following four variants were identified in the four probands and other family members with KC: heterozygous missense variation c.109G>A (p.Glu37Lys, rs369263247) in the procollagen-lysine, 2-oxoglutarate 5-dioxygenase 1 (PLOD1) gene; heterozygous missense variation c.3766G>A (p.Ala1256Thr, rs148216434) in the collagen type I alpha 1 (COL1A1) gene; heterozygous missense variant c.4364G>A (p.Gly1455Glu) in the collagen type V alpha 2 (COL5A2) gene; and missense variation c.976G>A (p.Glu326Ser) in the collagen type IV alpha 1 (COL4A1) gene. The above genotypes were co-segregated with corresponding phenotypes. All variations in these families appeared to be pathogenic.ConclusionFour variants in the PLOD1, COL1A1, COL5A2, and COL4A1 genes were identified in this study, which are collagen-coding genes and collagen crosslink regulatory genes and may be associated with the origin and development of KC. This study updates the knowledge of genes related to KC and the biomedical implications.